Determinants of the Public Debt and the Role of the Natural Resources: A Cross-Country Analysis - Elkhan Sadik-Zada; Andrea Gatto (Fondazione Eni Enrico Mattei (FEEM), 2019)
This paper investigates the major drivers of the public debt growth in 184 countries. The underlying cross-country survey is conducted on the basis of the improved compilation of datasets on the central government debt for 2013. The study finds that oil abundance, economic growth rate, the share of mineral rent in the total revenue, interest rate payments for foreign borrowings, and being a developing country have statistically significant impact on the growth of the public debt. In contrast, defense spending, unemployment rate, and inflation rate do not have a statistically significant positive impact on the public debt rate.
Keywords: F21; F34; F36; G15; H6; N1; F3; 330; Public debt; Oil rent; Mineral rent; Defence spending; Developing countries